Respostas

2014-03-02T17:23:35-03:00
E) 2x+5-5x= -1 
2x -5x = -1 - 5
-3x = -6
x= -6/-3 
x= 2
4x - 4 -5x = -6 + 90
4x - 5x = - 6 +90 + 4
- x= 92 * (-1)
x= - 92
desculpa kells a letra f confundi no lugar de 92 é 88.
Muito obrigado, me ajudou muiitoo...
2014-03-02T17:24:57-03:00
Letra e : 

2x+5-5x=-1
2x - 5x = -1 - 5
-3x = -6
x = -6 / -3
x = 2

Letra f : 

4x-4-5x=-6+90
4x - 5x = -6 + 90 + 4
-x = 88   .(-1)
x = -88

Letra g : 

-3x+10=2x+8+1
-3x - 2x = 8 + 1 - 10
-5x = -1
x = -1 / -5  = 1/5

Letra h : 

3x-4=11
3x = 11 + 4
3x = 15
x = 15 / 3
x = 5 

Letra i : 

4x+6= 12-2x
4x + 2x = 12 - 6
6x = 6
x = 6 / 6
x = 1

Letra j : 

x-10-8=2x+4
x - 2x = 4 + 10 + 8
-x = 22   .(-1)
x = -22

Letra k : 

5x+4x-10=2x-2
5x + 4x - 2x = -2 + 10
7x = 8
x = 8 / 7
1 5 1